Religion in early Stuart England, 1603-1638 an anthology of primary sources - Shuger, Debora K., 1953- (Documents of anglophone Christianity, 2012)
"A primary-source reader in early Stuart Christianity, reflecting the varieties of religious expression, theological conviction, and spiritual experience; the volume includes annotated and modernized (often for the first time) texts of sermons preached at court and in conventicles, bestsellers of practical divinity and private devotion, sacred lyrics, and ecclesio-political satires, doctrinal controversy and spiritual dialogues"--